(untitled) (Revista de Artes Marciales Asiáticas, 2019)
The doctoral thesis is one of the most valued productions in a researcher’s career. They are also an important source of information despite they are usually considered as grey literature due to their limited distribution. The aim of this work was to perform a bibliometric analysis of martial arts and combat sports (MA&CS) doctoral or postdoctoral dissertations indexed in the Bielefeld Academic Search Engine (BASE) database. A comprehensive MA&CS terms list and search strings were entered manually in the database search engine. Duplicate references were removed and obtained documents were filtered for meeting inclusion criteria. Selected references were then exported to Endnote X6 for classification and to Excel 2016 for bibliometric analyses. A total of 457 theses focused on MA&CS, published from 1951 to 2019, were retrieved. The last analyzed decade collected 64.55% of total documents and judo was the most studied MA&CS, with 90 documents. We conclude that MA&CS theses and dissertations are an important source of information for scholars and academics, especially since the amount of them has considerably increased during the last decade at the international level.